2016
DOI: 10.1089/met.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resveratrol Supplementation in Overweight and Obese Humans: A Systematic Review of Randomized Trials

Abstract: Based on the included studies, there is currently insufficient evidence to support the recommendation of resveratrol supplements in management of obesity. However, there were significant but not entirely consistent anti-inflammatory effects after resveratrol supplementation in overweight and obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
1
31
0
2
Order By: Relevance
“…In a recent meta‐analysis study including 28 trials, resveratrol supplementation showed a beneficial significant effect on weight, BMI, and WC without any significant effect on FM (Mousavi et al, ). Contrary to these findings, another meta‐analysis with fewer included studies found no significant effect of resveratrol administration on body weight and BMI (Christenson et al, ). Since our findings revealed a favorable effect of resveratrol on WC, FM, and trunk FM in unadjusted model, it seems that long‐term supplementation could affect these parameters in adjusted model.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent meta‐analysis study including 28 trials, resveratrol supplementation showed a beneficial significant effect on weight, BMI, and WC without any significant effect on FM (Mousavi et al, ). Contrary to these findings, another meta‐analysis with fewer included studies found no significant effect of resveratrol administration on body weight and BMI (Christenson et al, ). Since our findings revealed a favorable effect of resveratrol on WC, FM, and trunk FM in unadjusted model, it seems that long‐term supplementation could affect these parameters in adjusted model.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies have explored the effects of resveratrol in adipocytes, with variable effects on inhibition of cell proliferation, lipid accumulation, stimulation of apoptosis and effects on lipogenesis and lipolysis . As an obesity treatment, caloric restriction‐like and anti‐inflammatory effects of resveratrol have been described . However, initial enthusiasm and interest in this phytoalexin has dampened over the last years because translation from in vitro and animal studies into human trials proved problematic .…”
Section: Introductionmentioning
confidence: 99%
“…As an obesity treatment, caloric restriction‐like and anti‐inflammatory effects of resveratrol have been described . However, initial enthusiasm and interest in this phytoalexin has dampened over the last years because translation from in vitro and animal studies into human trials proved problematic . Also, many inconsistent biological effects were observed, in part due to variable exposure times and widely fluctuating doses used in cell culture systems, which are not always physiologically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…14 A review of resveratrol trials indicated that its supplementation is not sufficient for the management of obesity despite anti-inflammatory effects. 15 The levels of "pure" resveratrol used in short-term trials, if compared with those found in red wine, indicate consumption of well over 2 L of wine required to reach the equimolar levels, leading to health problems owing to alcohol levels consumed. 16 In observational studies, beneficial effects of red wine polyphenols are observed at low and moderate regular wine consumption levels, suggesting benefits are only partially owing to resveratrol.…”
mentioning
confidence: 99%
“…2 Even with doses that are exceeding physiologically relevant concentrations, evidence of cardiometabolic effects is inconclusive. 3,15 Therefore, whether moderate to high dosages will exhibit beneficial health effects without negative implications on gut barrier integrity and gut microbiota remains unknown. This might be further elucidated with technological and research advances in the -omics areas, where red wine polyphenols byproducts might be investigated from the population perspective.…”
mentioning
confidence: 99%